Ecdysis behaviors and circadian rhythm of ecdysis in the stick insect, Carausius morosus - Wadsworth, Tracy (J Insect Physiol, 2014)
Successful ecdysis in insects depends on proper timing and sequential activation of an elaborate series of motor programs driven by a relatively conserved network of neuropeptides. The behaviors must be activated at the appropriate times to ensure successful loosening and shedding of the old cuticle, and can be influenced by environmental cues in the form of immediate sensory feedback and by circadian rhythms. We assessed the behaviors, components of the neural network and the circadian basis of ecdysis in the stick insect, Carausius morosus. C. morosus showed many of the characteristic pre-ecdysis and ecdysis behaviors previously described in crickets and locusts. Ecdysis was described in three phases, namely the (i) preparatory or pre-ecdysis phase, (ii) the ecdysial phase, and (iii) the post-ecdysis or exuvial phase. The frequencies of pushups and sways during the preparatory phase were quantified as well as durations of all the phases. The regulation of ecdysis appeared to act via elevation of cGMP, as described in many other insects, although eclosion hormone-like immunoreactivity was not noted using a lepidopteran antiserum. Finally, C. morosus showed a circadian rhythm to the onset of ecdysis, with ecdysis occurring just prior or at lights on. Ecdysis could be induced precociously with mechanical stimulation.